The Incorporation of Employee Performance Appraisal into Organizational Development Strategies - Abdykalikova , Marta; Aikinbayeva , Gulden (Insight: the psychological dimensions of society, 2025)
The purpose of this study is to evaluate the effectiveness of scientifically based methods for assessing employee performance in modern organizations, particularly in the pharmaceutical industry. The research aims to integrate the evaluation process into the organization’s development strategy, ensuring alignment with both internal and external environmental factors. Furthermore, it focuses on examining the utility of jobEQ tests for measuring work attitudes, motivation, and emotional intelligence. Methods. The study employs a comprehensive review of existing literature on employee involvement and performance assessment, with a focus on identifying gaps in current methodologies. It also includes an analysis of jobEQ tools, specifically the Inventory for Work Attitude & Motivation (iWAM), COMET, and the Values Systems Questionnaire (VSQ), to evaluate their effectiveness in predicting employee behavior and performance in various job contexts. Results. The findings reveal that while various methods for assessing employee involvement exist, they often fail to account for the unique external and internal environments of organizational structures. The jobEQ tests, particularly iWAM and COMET/EQ, provide valuable insights into employee thinking styles, motivational preferences, and emotional intelligence, which are critical for aligning individual performance with organizational goals. Conclusions. To summarize, the integration of evidence-based employee performance evaluation methods with an organization’s development strategy is crucial for achieving strategic goals and enhancing overall effectiveness. The jobEQ tests offer a promising approach to measuring key aspects of employee engagement, but further research is needed to develop assessment tools that fully consider the complexities of both the external and internal organizational environment.